Phenology, Growth, Yield and Nitrogen Uptake of Wheat in Response to Nitrogen, Potassium and Their Application Methods: Effect of Nitrogen and Potassium on Growth of Wheat (Biological Sciences - PJSIR, 2021)
Application of macronutrients in less amount along with improper application method(s) are the major factors for low yield. Experiments were designed with the objectives to determine the optimum rate of nitrogen (N) and potassium (K) along with suitable application method to minimize nutrients losses. The experimental site was New Developmental Farm of the University of Agriculture Peshawar and  experiments were conducted for two consecutive years i.e. 2010-11 and 2011-12. After analysis, the results indicated that both N and K significantly affected days to phenology (anthesis and maturity). Days to phenology increased linearly with increase in rate of N and K and more days to phenology were recorded when both were at their highest rates. Similarly plant height, leaf area/tiller, flag leaf area, leaf area index, leaf area duration, grain yield, N uptake by grains and straw were increased with increasing level of N and K and attained maximum value when N and K was applied at the rate of 180 and 90 Kg/ha, respectively. Nutrients application method significantly affected plant height, leaf area/tiller, flag leaf area, grain yield and N uptake by straw and grains with maximum values for these traits were recorded when nutrients  (N and K) were applied in such a combination that 15% nutrients were supplied through foliar and 85% through soil application. Application methods had a non-significant effect on days to phenology, leaf area index and leaf area duration. It is concluded from the results that application of N and K at the rate of 180 and 90 Kg/ha respectively in such a way that 15% is applied through foliar spray and 85% through soil application improved growth, yield and N uptake of wheat crop under the semi-arid climate.